Epistolario, 1: gennaio 1906-dicembre 1922 - Ghetti, Noemi (International Gramsci Journal, 2023)
This is the first volume of the Epistolario (Correspondence), forming part of the National Edition of Antonio Gramsci’s Writings, includes letters both sent and received by Gramsci, nearly 160 of them, while others have come to light since this publication. The volume covers his period at school in Sardinia (Santu Lussurgiu and Cagliari), his university experiences and political – especially journalistic – activities in Turin, and the first part of his stay in Moscow as one of the representatives of the Italian Communist Party at the Third (Communist) International. There he was a member of the Comintern’s Executive Committee and, up to its Fourth Congress in November-December 1922, of the more restricted Presidium of the International. Ill health caused his stay, on and off, in a sanatorium at Serebrjanyj Bor (“Silver Wood”), then outside, and now in a suburb of, Moscow. He met there a fellow-patient, Evgenija Schucht, with whom, it transpires, he had some kind of amorous relationship. Through her, he met her younger sister, Julija, who interpreted for him at factory meetings in the textile town, Ivanovo-Voznesensk, where she was working, 250 kilometres from Moscow. As one of the appendices, the volume includes drafts of letters of Julija’s from this time, in the first stages of what became a partnership for life.